Hubungan Tingkat Stres Dengan Kadar Glukosa Darah Pada Pasien Diabetes Mellitus Tipe II Di RSPAD Gatot Soebroto - Silmi Ulyanah; Teti Hayati; Wilda Fauzia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Type II diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels and requires long-term management. In addition to physiological factors, psychological factors such as stress play a role in influencing blood glucose control. Objective: This study aims to analyze the relationship between stress levels and blood glucose levels in type II diabetes mellitus patients at Gatot Soebroto Army Hospital. Method: This study used a quantitative design with a cross-sectional approach. The study sample consisted of 102 outpatients with type II diabetes mellitus at the Internal Medicine Polyclinic of Gatot Soebroto Army Hospital, selected using an accidental sampling technique. Stress levels were measured using the Perceived Stress Scale (PSS) questionnaire, while blood glucose data were obtained from patient medical records. Data analysis was performed using the Chi-Square test with a significance level of 0.05. Results: The results of the Chi-Square test showed a significant relationship between stress levels and fasting blood glucose levels in type II diabetes mellitus patients (p = 0.001; p < 0.05). Conclusion: This study concludes that stress levels are significantly related to blood glucose levels, so stress management needs to be integrated into nursing care for patients with type II diabetes mellitus.